Audit Fees and Their Association with Audit Quality and Auditor Effort (gjstudies, 2019)
This research investigates the complex, non-linear relationship between auditfees, audit quality, and auditor effort, challenging the prevailing linear assumptionsin existing literature. We propose a novel methodological framework that integrates econometric analysis with computational simulation to model audit qualityas a multi-dimensional construct influenced by fee structures, regulatory environments, and technological adoption. Unlike prior studies that treat audit fees aseither a simple input or output variable, our approach conceptualizes fees as adynamic equilibrium point in a principal-agent relationship complicated by information asymmetry and technological mediation. We develop and test a tripartitemodel that distinguishes between fee adequacy, fee pressure, and fee premium, eachexerting distinct influences on auditor behavior and output quality. Our findingsreveal a threshold effect where moderate fee increases correlate with quality improvements up to an optimal point, beyond which diminishing returns and potentialquality degradation occur. Furthermore, we demonstrate how digital audit toolsand continuous monitoring systems, as referenced in contemporary audit literature,fundamentally alter the effort-quality-fee nexus by enabling more efficient evidencecollection and analysis. The study contributes original insights by identifying specific conditions under which fee variations signal different audit quality outcomes,providing auditors, audit committees, and regulators with a more nuanced understanding of fee structures’ implications. Our computational simulations, validatedagainst empirical audit data, offer predictive models for fee-quality relationshipsunder varying market conditions and technological implementations.